ANALISIS POTENSI POHON DI AREAL BEKAS TEBANGAN PT PUTRA KATINGAN PRATAMA DI KABUPATEN KATINGAN : John F. Gustaf, Gimson Luhan, V.S.G.Nyahu - JHT, Admin (Jurnal Hutan Tropika, 2016)
ABSTRACT Production forest management in Indonesia was developed using a pattern of forest concession since 70’s. Based on regulation of Ministry of Forestry No.11/2009, the silvicultural systems that be applied at the site were Indonesian Selective Cutting and Planting (TPTI), Selective Cutting and Strips Planting (TPTJ), Gap Cutting (Tebang Rumpang), and Clear Cutting with Artificial Regeneration (THPB). In connection with that, there are activities of timber, cruising 2-5% in the working areas of PT. Pratama Putra Katingan to obtain details about the condition of standing stock at the forest. They are conducted every 10 years. The observation results of commercial standing stock for diameter ? 20 cm namely 45.20 stems/ha and volume of 19.65 m3/ha, meanwhile the total standing stock of forest namely 72.70 stems/ha and volume of 40.75 m3/ha. Keywords: Commercial species forest concenssion, standing stock